Grondtrekke van Adrio König se teologie - S. A. Strauss (Acta Theologica)
In 2001 Adrio König published a book Focus on 300 questions about faith, which most people ask (title translated). Basically this book can be regarded as a summary of König’s systematic theology. König’s theology is so stimulating that it deserves research. This article analyses Focus, with reference to other books by the same author, aiming at disclosing the basic features of his theology. The article concludes that König’s theology can be described, from a reformed perspective, as ambiguous: biblical as well as contextual, confessional as well as ecumenical. König describes his theology as “eschatological covenant theology”. The positive and negative implications are also discussed.